Condition monitoring of circuit breakers: Current status and future trends - Feizifar, Behnam; Usta, Omer (IEEE, 2017)
Circuit breakers (CBs) as vital switching equipment are utilized throughout the power system. The reliable operation of CBs are of utmost importance. Unplanned failures of CBs could result in catastrophic consequences for valuable equipment in the electricity grid. This paper presents a systematic review of recent research and developments regarding the condition assessments of CBs. Brief explanations to various techniques are discussed and an analytical perspective towards the real-time condition monitoring of CBs is recommended for the future work.